Evaluation of the hepatroprotective and nephroprotective activities of Scrophularia hypericifolia growing in Saudi Arabia - Alqasoumi, Saleh I. (2013)
The hepatroprotective and nephroprotective effects of the ethanol extract of the aerial parts of Scrophularia hypericifolia growing in Saudi Arabia were evaluated at 250 and 500 mg kg(−1) doses using Wistar albino rats as experimental animal model. Toxic doses of paracetamol were used to induce liver and kidney toxicities, while the standard drug silymarin was used as reference. The biochemical parameters such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma glutamyl transpeptidase (GGT) and total bilirubin were estimated as reflections of the liver condition. Kidney condition was investigated through measurement of serum urea, serum creatinine, sodium and potassium levels. Liver and kidney samples of rats treated with 500 mg kg(−1) of the extract were subjected to the histopathological study. The ethanol extract of the aerial parts of S. hypericifolia showed dose dependent moderate level of protection against paracetamol induced hepatrotoxicity and nephrotoxicity as indicated from the obtained results. The reduction of the sodium and potassium levels by the higher dose of the extract exceeded that obtained by silymarin.